Performance test of vacuum frying machine technology in mango skin chips frying process - Mufarida, Nely Ana; Abidin, Asroful (Universitas Muhammadiyah Metro, 2021)
Nowadays, the business of processing fruit flesh into various snacks has been done a lot, but still, a few are starting to look at the use of fruit skins. If usually people are only interested in the use of fruit flesh, creative people will start to be interested in utilizing the fruit skin waste that people usually throw away. One of them is the use of mango peels into fruit chips. By frying and varying the taste of the mango peel, it can create a snack that is different from the others. So that it attracts consumers to consume this snack. The processing of fruit into chips needs technological support so that the quality of the chips produced is acceptable to consumers. One of the ways to produce healthy food without changing its original form is to use vacuum frying technology. Compared to conventional frying, the vacuum system produces a much better product in terms of appearance, color, aroma, and taste. Based on the above, this study discusses the performance test of vacuum frying technology in the utilization of abundant mango peel waste into products that have selling value. height and longer shelf life by making the mango peel into chips so that the economic value of the fruit can be increased. In this study, researchers used direct observation for data collection techniques from the results of research, namely a technique or data collection method by making direct observations on the Vacuum Frying Machine which was tested by recording the results of the observations. The research was conducted in 2 stages, namely preliminary research and main research. Preliminary research was conducted to determine the optimal temperature and frying time range for the mango peel chips used in the frying process. The observations made in the preliminary study were subjective observations of the color and crunch of the mango skin chips. The best results from the preliminary research are used in the main study. Determination of the best frying temperature and time from the results of the organoleptic test by weighing test. In the organoleptic test, the panelists were asked for their opinion regarding the level of their preference for mango skin chip products. The organoleptic test in this study used 15 panelists with the preference test covering 4 quality parameters, namely aroma, taste, crispness, and color.Keywords: Performance Test, Vacuum Frying Machine, Mango Skin Chips